A comparison of pre-service teacher educational modes: taking China, the United States, Canada and Singapore as examples - Yanmei, Zhao; Muhamad, Mohd Mokhtar; Mustakim, Siti Salina (Human Resources Management Academic Research Society (HRMARS), 2024)
In globalization, pre-service teacher (PST) educational modes in different countries reflect unique cultures, educational traditions and social needs. In-depth comparisons and analyses of these modes can provide cross-cultural educational insights to help countries learn, borrow and innovate in teacher education. This study explores and compares PST educational modes in China, the United States, Canada and Singapore, with particular attention to the characteristics, strengths and limitations of these modes and how they are adapted to their respective cultural and social needs. A comparative analysis approach is adopted to analyze these countries' educational modes, cultural backgrounds and policy environments through systematic collection and collation of relevant literature and then to draw out the differences and commonalities of the different methods. It is found that the PST educational modes in each country are closely related to their cultural and educational traditions and reflect a shift in the role of teachers from traditional knowledge transmitters to facilitators of learning, and promoters of technology play a vital role in teacher education and pose challenges. Countries have recognized the importance of lifelong learning in developing the teaching profession. These findings emphasize the importance of cultural differences in educational practices, and educational policymakers must understand and respect these differences when designing teacher education policies and procedures. At the same time, there is a need to focus on the impact of technological advances on education and to improve teacher resilience and the quality of teaching through policies and practices that support lifelong learning.